(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Entrepreneurship acts as a vital element inthe organization of economies. This did not occur simultaneously in alldeveloping countries. Differences in growth rates are often attributed todifferences in the speed with which countries embrace entrepreneurial energy.This paper aims to highlight the various contributions to the entrepreneurshipliterature from the perspective of economic growth and also the contribution ofMadhya Pradesh in the entrepreneurship development and industrial awakening.Entrepreneurship is acknowledged as a driver for economic growth, competitiveness,and job creation.